Jamaica : Technical Assistance Report-Cartac Report on the Sector Accounts and Balance Sheets Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses the findings and recommendations of the IMF's Statistics Department mission for Jamaica concerning sector accounts and balance sheets. Jamaica had made considerable progress toward many items in the August 2015 IMF mission action plan. The Bank of Jamaica (BOJ) has prepared quarterly sector financial balance sheets for nearly all financial sectors. Most of these data are available on a from-whom-to-whom basis. The BOJ also prepares positions data for the rest of the world and obtains balance sheet data for several of the larger nonfinancial corporations (both public and private). These data have all been compiled from March 2013 to March 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet